Study on the Prevalence of Multidrug- resistant and In vitro Biofilm Formation among Uropathogenic Escherichia coli from Clinical Isolates - Wesam Elsayed Gawad; Abdelgawad Mohamed Hashem; Omneya Mohamed Helmy; Wael Mostafa Tawakkol (Cairo : Wesam Elsayed Gawad, 2018)
Two hundred and twenty eight UTIs clinical isolates were collected from two Egyptian governorates and identified by conventional culture methods and by the PCR amplification of uspA gene, and classified into the corresponding phylogenetic groups by multiplex PCR. Antimicrobial susceptibility testing was performed using the Kirby-Bauer method. PCR detection of the main genes of the AcrAB-TolC efflux pump was carried out. The contribution of efflux pump-mediated resistance to MDR phenotype was detected by the efflux pump inhibitor microplate-based assay. The ability for in-vitro biofilm formation in UPEC isolates was also tested. The minimum inhibitory concentration (MIC) of tested antibiotics was detected in the presence and absence of sub-inhibitory concentration of EDTA (2 mM) by the two-fold broth microdilution method. The ability for in-vitro biofilm formation was detected in the absence and the presence of 2 concentrations of EDTA (10 mM and 20 mM). The effect of polyvinylchloride Gelatin-EDTA coat on biofilm formation by strong and moderate biofilm producers was also tested. One hundred and seventy five isolates were presumptively identified as E.coli by conventional culture methods, and confirmed by the PCR amplification of uspA. The phylogenetic analysis of the UPEC isolates revealed that most of the isolates belonged to phylogenetic groups B2 (64.57%) and D (18.85%). MDR phenotype was detected in 90.8 % of UPEC isolates. Efflux pump mediated resistance was detected in all MDR isolates. The acrA, acrB and tolC genes were concomitantly detected in 74.84% of MDR isolates. The ability for in vitro biofilm production was recorded in 76.5% of UPEC isolates. The addition of 2 mM EDTA along with antibiotics resulted in a decrease in the antimicrobials MIC values. The highest inhibitory effect of EDTA was observed with meropenem, rendering (81%) of resistant UPEC isolates to completely sensitive ones. EDTA with a concentration of 10mM, 20 mM and Gelatin-EDTA coat inhibited biofilm formation in strong and moderate biofilm producers by 45.8 %, 78.8 % and 81.1%, respectivelybiofilm are needed
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Multidrug- resistant; PCR; Uropathogenic Escherichia coli